2020
DOI: 10.1002/jccs.202000364
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of vitamin B6 and ciprofloxacin using polyurethane foam in pure and pharmaceutical preparations: Kinetic and equilibrium studies

Abstract: The release of active pharmaceutical ingredients and their metabolites in surface waters and groundwater with insufficiently treated wastewaters nowadays may be a global environmental concern. In this study, simple, inexpensive, and solid phase procedure has been developed for the removal of pyridoxine hydrochloride (vitamin B 6 , PDX) and ciprofloxacin (CPX) onto polyurethane foam (PUF) using the batch mode technique. PUF was characterized using scanning electron microscopy and FT-IR spectroscopy. The batch e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…The trend observed in this study appears to be similar to the general pH trend found for the sorption of CIP onto polyurethane foam. The possible interactions between CIP and polyurethane foam were evaluated similarly by considering pKa 1 and pKa 2 values of CIP and surface charge of the sorbent material 50 …”
Section: Resultsmentioning
confidence: 99%
“…The trend observed in this study appears to be similar to the general pH trend found for the sorption of CIP onto polyurethane foam. The possible interactions between CIP and polyurethane foam were evaluated similarly by considering pKa 1 and pKa 2 values of CIP and surface charge of the sorbent material 50 …”
Section: Resultsmentioning
confidence: 99%
“…When the adsorption process was finished, magnetic field was applied to separate the adsorbent, and the remanent liquid was taken to measure the absorbances on UV. The adsorbance (q) and the removal efficiency (η) of the nanomaterials were calculated on the basis of equations (1) and (2) [31].…”
Section: Adsorption Experimentsmentioning
confidence: 99%